2021
DOI: 10.1016/j.ultrasmedbio.2020.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Feasibility of X-ray Guided Non-Invasive Ablation of the Medial Branch Nerve with Focused Ultrasound: Preliminary Proof of Concept in a Pre-clinical Model

Abstract: Four to six million patients a year in the United States suffer from chronic pain caused by facet joint degeneration. Thermal ablation of the affected facet joint's sensory nerve using radiofrequency electrodes is the therapeutic standard of care. High-intensity focused ultrasound (HIFU) is a novel technology enabling imageguided non-invasive thermal ablation of tissue. Six pigs underwent fluoroscopy-guided HIFU of the medial branch nerve and were followed up for 1 wk (two pigs), 1 mo (two pigs) and 3 mo (two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Prior technical validation analyses and in vivo preclinical studies in a large animal model in which this fluoroscopy-guided HIFU system was used provided evidence for the safe and effective ablation of the MB in the present study [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Prior technical validation analyses and in vivo preclinical studies in a large animal model in which this fluoroscopy-guided HIFU system was used provided evidence for the safe and effective ablation of the MB in the present study [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 90%
“…A tissue-destructive HIFU sonication was then performed with energies of 1,000 J to 1,500 J for 50 seconds per treatment site. With similar technical parameters used, previous data from preclinical, simulation, and cadaver studies showed the expected temperature at the targeted area to reach 100 degrees Celsius [ 12 ]. On the basis of histology from pigs euthanized at 1 week after the procedure, the average lesion size was 16 × 8.8 mm in the shape of a “Hershey’s Kiss” chocolate, with the flat base along the bony surface [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIFU destroys the tumor target tissue at depths inside the body at a focal point without damaging adjacent tissues or intervening vital structures [ 1 ]. This damage is caused by ultrasonic thermal coagulation and destructive mechanical effects, including acoustic cavitation [ 2 ]. HIFU devices rely mostly upon ultrasonic heating under continuous or long pulse irradiation [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…In thermal ablation, the focal intensity needs to be high enough to denature protein and cause coagulative necrosis [ 4 5 ]. The latest technology, called “histotripsy,” uses HIFU bursts of higher amplitude but shorter duration to enhance acoustic cavitation [ 2 6 7 ]. HIFU appears to be an attractive therapy.…”
Section: Resultsmentioning
confidence: 99%